Operational considerations for approximating molecular assembly by Fourier transform mass spectrometry - Weiss, Gabriella M.; Asche, Silke; McLain, Hannah; Chung, Angela H.; Mehr, S. Hessam M.; Cronin, Leroy; Graham, Heather V. (Frontiers in Astronomy and Space Sciences, 2024)
Some of the most common life detection techniques for planetary exploration focus on organic molecule characterization, but life on other planets may not chemically resemble that found on Earth. Therefore, an agnostic detection system of signs of life (biosignatures) is essential. Assembly Theory (AT) is a conceptual tool for understanding evolution and object formation that has been useful in developing an approach to quantify molecular complexity via the Molecular Assembly index, which when combined with abundance, allows the total assembly number of a sample to be calculated. Because AT makes no assumptions about the chemistry of life, it is an agnostic tool that identifies molecular structures that are probabilistically more likely to have arisen via selection and therefore biological processes. AT uses graph theory to quantify molecular complexity by finding the shortest sequence of joining operations (e.g., chemical bonds) required to build a compound from a set of starting materials allowing recursive reuse of units or fragments. For molecules, this number of steps is the MA value. We explore the use of Fourier transform (i.e., Orbitrap) mass spectrometry for approximating MA by quantifying how a molecule breaks apart into fragments. We analyze amino acid and nucleoside standards individually and as mixtures, as well as amino acids from naturally occurring biological and meteoritic sources. Aside from sample type, we evaluate the effect of analyte concentration and fragmentation energies on the generated MA value. Additionally, an older Orbitrap model similar to flight prototype instrumentation, was tested. The raw mass spectrometry data was compared with two different MA processing algorithms - one that uses the parent molecule spectrum and molecular weight (recursive) and one that does not (non-recursive). Concentration, fragmentation energy, and sample type all influence the raw mass spectra. However, the recursive algorithm reports MA estimates that are more consistent across sample types, concentrations, and fragmentation energies. We discuss instrument requirements for approximating MA that can be applied to future flight and sample return missions.